Detecção de anticorpos IgG ANTI-Neospora caninum em diferentes grupos de pacientes imunodeprimidos - Lobato, Janaina (2006)
Little is known about the epidemiology of N. caninum infection in humans, particularly in populations with high T. gondii infection rates. This study aimed to investigate the presence of antibodies to N. caninum in Toxoplasma-seropositive and -seronegative individuals. Serum samples from 331 individuals were tested for the presence of IgG antibodies against N. caninum and T. gondii by indirect fluorescent antibody test (IFAT), enzyme-linked immunosorbent assay (ELISA) and Western blot (WB). Serum samples were divided into 5 groups, as follows: 65 from HIV-positive patients; 62 from allograft transplantation patients; 87 from cancer patients; 53 from hemodialysis patients; and 64 from blood donors. Seroreactivity to N. caninum was confirmed by WB, and the criterion for positivity was the sera recognition of at least two out of three immunodominant antigens (17, 29 e 35 kDa) from the parasite. Seropositivity to N. caninum was predominantly seen in HIV-patients (28%), whereas significantly low seropositivity was detected in blood donors (5%). Intermediate rates were seen in cancer (13%), hemodialysis (11%), and allograft transplantation (7%) patients. Seropositivity to N. caninum in the three groups with higher seropositivity rates was significantly associated with seropositivity to T. gondii. The results of this study indicate the presence of N. caninum exposure and seroconversion in humans, particularly in HIV patients, who could have opportunistic and concurrent infections with T. gondii. These findings may bring a new concern for the unstable clinical health of HIV patients and the actual role of N. caninum infection in immunocompromised patients.